A novel scheduler for concurrent Tx/Rx wireless mesh networks with weighted links - Chin, Kuek; Soh, Sieteng; Meng, C. (IEEE Communications Society, 2012)
This paper considers the NP-hard problem of scheduling weighted links in concurrent transmit/receive wireless mesh networks. The problem generalizes existing works to links with weight wij ≥ 1. We propose an O(|V|2) algorithm, where V is the set of routers, that is orders of magnitude faster than computationally intensive approaches that use the well-known Goemans-Williamson (GWA)'s maximum cut algorithm and also brute-force. Our algorithm generates schedules, on average, with at most 3% and 9% fewer links than the GWA and brute-force approaches respectively.